Weight change adjusted equations for assessing resting metabolic rate in overweight and obese adults. Issue 3 (May 2021) - Nachmani, Moran; Lahav, Yair; Zeev, Aviva; Grosman-Rimon, Liza; Eilat-Adar, Sigal
Highlights: RMR reduction during weight loss is greater than expected. The most accurate prediction equation for RMR loss was developed by Ravussin and Bogardus [10 ]. Different equations by gender–before and after weight loss, were suggested. The new suggested equation for RMR was the most accurate in women after weight loss. The new suggested equation for RMR was the most accurate in men before weight loss. Abstract: Background: Although over one hundred equations have been developed to predict the energy expenditure of individuals, none are sensitive to weight change in assessment of resting metabolic rate (RMR) before and after weight loss. Objective: To formulate adjusted equations for overweight and obese individuals and to compare their accuracy with existing prediction RMR equations before and after weight loss. Subjects/materials: This is historical prospective study. Participants included 39 overweight and obese men and women before and after losing 10–20% from baseline weight on a diet and physical activity regimen for at least three months. Pre and post weight loss measured RMR results were compared to estimated RMR using several existing prediction equations: Harris and Benedict, Ravussin and Bogardus, and Mifflin et al. To improve the accuracy of these prediction equations, we suggest new equations adjusted for weight loss, based on measured RMR and evaluated their accuracy. Results: Pre and post weight loss data indicated: significant fat reduction in both genders; reduction in free-fat mass only in men, and a significant decrease in measured RMR only in women. Our suggested equations were the most accurate and closest to measured RMR in both genders, in comparison to the Harris and Benedict, Ravussin and Bogardus, and Mifflin et al equation results. Estimated RMR using the latter equations was significantly lower than measured RMR in both genders at pre and post weight loss (P < 0.01). Conclusions: This study highlights the need for adjusting RMR equations before and after weight loss in overweight and obese individuals. Further research is needed to validate our suggested equations.